Children Right Protection from Brawl (Junivenille Delinquency) Violence Content in Social Media - Muhamad Nazarudin (Journal Research of Social Science, Economics, and Management, 2023)
Protection from brawl Juvenille Deliquency violence content in social media is defined as children right and it is arranged in many Indonesia regulation law. But in fact, children can access the violent content easily from their social media. This writingis aim to examine influence of brawl Juvenille Deliquency violence content to children establishment. Method used in this research is qualitative with are data condensation, display, drawing and verifying conclusion processing technic. The result show that the violation of children right by brawl Juvenille Deliquency violence content is frequently happen in social media. Its give the negative impact because its appeling violence behavior to the children, which in long term can make them involve to criminal activity. The protection act is urgently need to take from the parent and the government.